Synthesis of Biochar From Lignocellulosic Biomass for Diverse Industrial Applications and Energy Harvesting: Effects of Pyrolysis Conditions on the Physicochemical Properties of Biochar - Mukherjee, Alivia; Patra, Biswa R.; Podder, Jiban; Dalai, Ajay K. (Frontiers in Materials, 2022)
The excessive dependency on fossil fuel resources could be curtailed by the efficient conversion of lignocellulosic biomass. Biochar, a porous carbonaceous product synthesized exploiting thermochemical conversion pathway, could be an environment-friendly replacement of fossil fuel resources. Slow pyrolysis, a sub-class among various thermochemical conversion techniques, has gained immense popularity owing to its potential to convert biomass to biochar. Furthermore, biochar obtained as the by-product of slow pyrolysis has attracted enormous popularity due to its proven role and application in the multidisciplinary areas of engineering and environmental remediation applications. The physicochemical quality of biochar and its performance is significantly dependent on the feedstock type and pyrolysis process parameters. Therefore, further experimental research and investigations in terms of lignocellulose biomass type and pyrolytic process parameters (temperature, heating rate and reaction time) are essential to produce biochar with desired physicochemical features for effective utilization. This review presents an updated report on slow pyrolysis of lignocellulosic biomass, impact of different pyrolysis parameters and degradation pathway involved in the evolution properties of biomass. The influence of the feedstock type and lignocellulosic composition on the biochar properties are also discussed meticulously. The co-relationship between biochar yield at different pyrolysis temperatures and the development of textural properties provides valuable information for their effective utilization as a functional carbon material. Additionally, an extensive study was undertaken to collate and discuss the excellent physicochemical characteristics of biochar and summarizes the benefits of biochar application for diverse industrial purposes. Biochar is acknowledged for its excellent physicochemical properties owing to the thermal treatment and as a result its prospective diverse industrial applications such as for soil treatment, carbon sequestration, adsorbent (wastewater treatment or CO2 capture), producing activated carbon for gold recovery, energy storage and supercapacitor are summarized systematically in this review paper. For instance, biochar when applied in soil have shown improvement in soil respiration by 1.9 times. Furthermore, biochar when used to capture CO2 from flue gas stream under post-combustion scenario has demonstrated superior capture performance (2.8 mmol/g) compared to commercial activated carbon. This paper identified the knowledge gaps and outlooks in the field of the advancements of biochar from slow pyrolysis for targeted engineering applications mainly in the field of environmental remediation and energy harvesting.